Peran Solo International Performing Art (SIPA) Sebagai Penguatan Branding Solo The Spirit Of Java - Nur Dewati; Dr. Meitolo Hulu, S.ST., M.M. (Politeknik Pariwisata NHI Bandung, 2023)
Solo International Performing Art (SIPA) is a tourism event held in Solo, Central Java. SIPA is one of the pioneers and a legendary event and continue for 15 years. SIPA is a leading event, involving international delegations and becoming the icon of the Solo City cultural festival. The Solo Government has the brand “Solo The Spirit Of Java” which has been used for 17 years and is still considered very relevant. This research wants to see how SIPA as a leading event contributes to strengthening the branding